2016
DOI: 10.1111/apha.12684
|View full text |Cite
|
Sign up to set email alerts
|

Day‐restricted feeding during pregnancy and lactation programs glucose intolerance and impaired insulin secretion in male rat offspring

Abstract: We conclude that out-of-phase feeding during pregnancy and lactation can lead to glucose intolerance in male offspring, which is caused by a disruption in insulin secretion capacity. This metabolic programming is possibly caused by mechanisms dependent on miRNA modulation of syntaxin 1a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…In agreement with our fetal data, maternal obesogenic diet during pregnancy and lactation resulted in reduced abundance of both IRS1 and the p110β subunit of PI3K in adult rodent offspring skeletal muscle (32) and adipose tissue (33). Further, IRS1-PI3K activity, but not IRS1 phosphorylation, was reduced in fetal muscle in offspring of obese sheep (34); although, these measures in fetal sheep were made in fasted, and not insulin-stimulated tissues, it provides additional evidence that IRS1-PI3K may be a critical node regulated by maternal obesity in the fetal muscle.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our fetal data, maternal obesogenic diet during pregnancy and lactation resulted in reduced abundance of both IRS1 and the p110β subunit of PI3K in adult rodent offspring skeletal muscle (32) and adipose tissue (33). Further, IRS1-PI3K activity, but not IRS1 phosphorylation, was reduced in fetal muscle in offspring of obese sheep (34); although, these measures in fetal sheep were made in fasted, and not insulin-stimulated tissues, it provides additional evidence that IRS1-PI3K may be a critical node regulated by maternal obesity in the fetal muscle.…”
Section: Discussionsupporting
confidence: 92%
“…This proposition is corroborated by studies showing that forced physical activity (swimming) during the light phase fails to modulate nocturnal melatonin production in rats [42]. We and others have also previously shown that light phase-restricted feeding with standard chow fail to reduce melatonin metabolite in the urine or melatonin circulating levels during the dark phase [43,44]. On the other hand, the daytime consumption of carbohydrates by rodents seems to be particularly relevant to yield reductions in nocturnal melatonin production.…”
Section: Discussionsupporting
confidence: 59%
“…It was therefore of interest to discover that restricting food availability of pregnant rats to the inactive day period can impair metabolic outcomes in progeny (3). Exposure of rat dams to a day-restricted feeding protocol through gestation and lactation programmed poor glucose tolerance and reduced glucose stimulated insulin secretion of pancreatic islets in the male offspring (3).…”
Section: Maternal Chronodisruption and Progeny Metabolic Healthmentioning
confidence: 99%